Numerical simulation of heat transfer on nanofluid flow in an annular pipe with simultaneous embedding of porous discs and triangular fins. (17th February 2021) - Poursharif, Zohreh; salarian, Hesamoddin; Javaherdeh, Kourosh; Eshagh Nimvari, Majid
ABSTRACT: In the present study, the effect of simultaneous embedding of triangular fins and porous discs inside an annular pipe on the heat transfer rate is studied. The nanofluid turbulent flow enters the space between the two pipes. Various factors such as the effects of cross-sections of porous disc coverage ( S = 0.76, S = 0.42), fin height ( H ), and the nanoparticles volume fraction on the heat transfer rate and the thermal performance are examined. The results show the increase in the heat transfer rate in an annular pipe containing triangular fins and porous discs at S = 0.42 has its maximum value when H = 0.33, but at S = 0.76 the maximum heat transfer rate occurs in H = 0.267. The increases in the Nusselt number in both cases are high enough to compensate for the pressure loss due to the flow so that the thermal performance would be greater than 1. The results also reveal that the increase in the volume fraction leads to an increase in the Nusselt number, while the increase in the pressure loss at high Reynolds numbers dominates the increase in the heat transfer and causes the thermal performance to become less than 1.